Sam Wanamaker : a global performer - Devlin, Diana (Oberon Books Ltd, 2019)
Actor. Director. Activist. Sam Wanamaker is best known as the man who spent the last twenty five years of his life reconstructing Shakespeare's Globe near its original site just south of the Thames in London. Tragically, he died four years before its Gala Opening in 1997. Born in the USA, he began his acting career in travelling shows before moving on to Broadway. A vocal left wing activist, Wanamaker moved to the UK, fearful of being blacklisted during the McCarthy witch hunts of the early 1950s. Having crossed the Atlantic, he carved a successful and varied career as both actor and director, but continued to be outspoken on a variety of topics, including racial discrimination in the theatre. With his staunch sense of purpose, he made as many enemies as friends: charismatic and persuasive, he was also stubborn and domineering. But it was these very qualities that made his lasting legacy, Shakespeare's Globe, a reality, despite many battles. The fascinating life of Sam Wanamaker is explored for the first time in this biography by Diana Devlin, who worked closely with him for his last twenty years.